Workforce Location and Equilibrium Unemployment in a Duocentric Economy with Matching Frictions - Etienne Lehmann; Paola L. Montero Ledezma; Bruno Van der Linden (Center for Economic Studies and ifo Institute (CESifo), 2015)
This article examines unemployment disparities and efficiency in a densely populated economy with two job centers and workers distributed between them. We introduce commuting costs and search-matching frictions to deal with the spatial mismatch between workers and firms. In a decentralized economy job-seekers do not internalize a composition externality they impose on all the unemployed. With symmetric job centers, a change in the distribution of the workforce can lead to asymmetric equilibrium outcomes. We calibrate the model for Los Angeles and Chicago Metropolitan Statistical Areas. Simulations suggest that changes in the workforce distribution have non-negligible effects on unemployment rates, wages, and net output, but cannot be the unique explanation of a substantial mismatch problem.
Keywords: J64; R13; R23; 330; spatial mismatch; commuting; urban unemployment; externality